Enzymatic Saccharification of Sugarcane Bagasse Using Ash - Supplemented Hydrogen Peroxide as Pre-Treatment - Odisi, Estácio Jussie; Lima, André Oliveira de Souza; Colonetti, Vivian; Alves, Rômulo Couto; Gilioli, Andressa; Quadri, Mara Gabriela Novy (International Journal of Advanced Engineering Research and Science, 2022)
Purpose: Enzymatic saccharification of sugarcane bagasse with cellulases was investigated after hydrogen peroxide pretreatment. Methods: Two pretreatments, alkaline hydrogen peroxide and hydrogen peroxide supplemented with ash were compared in their performance in the improvement of the susceptibility of bagasse to enzymatic action. The reaction yield was evaluated by the reducing sugar content released from the pretreated bagasse after 48 hours of enzymatic hydrolysis, and the best condition was found for both treatments. Results: The yield, expressed in reducing sugars for the alkaline hydrogen peroxide pretreatment was 217.6 mg g-1 bagasse, and 179.9 mg g-1 bagasse for hydrogen peroxide ash pretreatment; the untreated bagasse provided 74.3 mg g-1 bagasse yield, showing the effectiveness of the two pretreatments. Conclusion: The pretreatment with hydrogen peroxide supplemented with ashes appears more feasible for implementation since alkali addition in the pretreatment delivers many caustic residues that need expensive washing process and generate aggressive effluents into the environment; besides alkali addition promotes partial degradation of hemicellulose.